2019
DOI: 10.1002/mawe.201800208
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of geometrical structure and morphology of samples made of hard machinable materials after wire electrical discharge machining and vibro‐abrasive finishing

Abstract: In this article the results concerned influence of processing conditions of the wire electrical discharge machining and vibro‐abrasive machining on the surface layer and morphology of samples made of hard machinable materials used in aircraft industry like: Titanium 5553 β, Inconel 617, Hastelloy X and Magnesium AZ31 have been presented. For this purpose the cubic and cylindrical samples made of hard machinable alloys have been prepared using optimal electric parameters of wire‐cut electrical discharge machini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Machining time, however, remains the main disadvantage of WEDM. Therefore, it is expected to be adopted in single and small-lot production [ 38 , 113 ]. Currently, wire electrical discharge machining is entering new industry sectors that were previously inaccessible.…”
Section: Methods Of Manufacturing Fir Tree Slots Of the Turbine Discsmentioning
confidence: 99%
“…Machining time, however, remains the main disadvantage of WEDM. Therefore, it is expected to be adopted in single and small-lot production [ 38 , 113 ]. Currently, wire electrical discharge machining is entering new industry sectors that were previously inaccessible.…”
Section: Methods Of Manufacturing Fir Tree Slots Of the Turbine Discsmentioning
confidence: 99%
“…The research was carried out using surface grinder SPG 30x80. The samples in shape of rectangle of dimension 10 mm × 50 mm were cut using wire electrical discharge machining (WEDM) technology [8]. The samples were plunge-grinded without using cooling liquid (CL).…”
Section: Work-stand Methods and Experimental Conditionsmentioning
confidence: 99%
“…Experimental analysis carried out to examine the significant factor in wire-EDM that led to the existence of thick recast layer with 5 to 9 μm thickness in Inconel superalloys [15]. Some findings concerning the effect of machining methods on surface morphology and stereo-metric surface parameters in wire-EDM of hard machined materials which also include Inconel alloys, are discussed [16]. Simultaneously, several studies can be reported in literature that discusses the challenges correlated with precision machining of different materials with wire-EDM [17].…”
Section: Related Workmentioning
confidence: 99%